Cardiac microcalcifications in transthyretin (ATTR) amyloidosis. (1st April 2022) - Thelander, Ulrika; Westermark, Gunilla T.; Antoni, Gunnar; Estrada, Sergio; Zancanaro, Alice; Ihse, Elisabet; Westermark, Per
Abstract: Background: Bone tracers bind to amyloid-containing heart of most patients with ATTR amyloidosis. Amyloid deposits outside the heart are often scarce and bone scintigraphy is increasingly often used to diagnose cardiac involvement. However, the nature of the binding of bone tracers to the heart is not clear. Objective: To identify possible calcium deposits in hearts with amyloid, explaining bone tracer binding. Methods and results: Formalin-fixed and paraffin embedded cardiac specimens from three patients with ATTR and one with AL amyloidosis, all with cardiac deposits, were studied. The specimens covered large parts of the heart. Sections were stained immunohistochemically for ATTR deposits and according to von Kóssa for calcifications. The study identified in all hearts, but particularly in the ATTR materials, focal, tight swarms of tiny calcifications. These were sometimes associated with amyloid but found as frequent in areas without such deposits. Autoradiography with [ 99m Tc]Tc labelled 3, 3-disphos-phono-1, 2-propanodicarboxylic acid (DPD) revealed labelling in von Kóssa positive areas. Electron microscopically the particles were not amorphous but had a complex structured appearance and were often surrounded by a membrane, indicating a cellular origin. Labelling with antibodies against ubiquitin and P62 pointed to result from autophagy. Conclusions: Our study indicates that binding of skeletal probes to amyloid-containing hearts depends on an irregular presence of clouds of very tiny calcifications, which seem not to be directly associated with amyloid fibrils. Therefore, [ 99m Tc]Tc-DPD bone scans can be considered surrogate markers of ATTR amyloid but have to be used carefully to estimate amyloid amount or disease progression. Highlights: Tight clusters of microcalcifications occur particularly in the atrio-ventricular cardiac regions in ATTR amyloidosis The individual calcifications have a structured appearance, indicating cellular origin and bind DPD The microcalcifications are not directly associated with amyloid fibrils. DPD bone scans can be considered surrogate markers of transthyretin amyloid